Impact of common institutional ownership on enterprise digital Transformation—Collaborative governance or collusion fraud? - Wennanxiang Wang; Ridong Hu; Cheng Zhang; Yang Shen (Heliyon, 2023)
As a crucial external capital force of enterprises, common institutional ownership plays an essential role in enterprise innovation and development. However, few studies have focused on the impact and underlying impact mechanisms of common institutional ownership on the digital transformation of enterprises. Hence, this study uses Python to analyse the annual reports of listed companies from 2007 to 2021 and constructs measures of enterprise digital transformation. Then, based on panel fixed effects Poisson regression, this study examines the influence of common institutional ownership on enterprise digital transformation by using theoretical logic and empirical evidence. The results reveal that common institutional ownership significantly inhibits enterprise digital transformation; this result remains valid after a series of endogeneity and robustness tests, thereby indicating that common institutional ownership exerts a collusion fraud effect. The mechanism analysis shows that common institutional ownership hampers enterprise digital transformation mainly by increasing monopoly power within the market, aggravating information asymmetry between enterprise insiders and outsiders, and intensifying executive self-dealing. Further analysis reveals that the inhibitory effect of common institutional ownership on digital transformation is more significantly negative in the case of non-state-owned enterprises versus state-owned enterprises. This study expands the research on the factors influencing enterprise digital transformation. The results provide a helpful reference for further improving institutional investors’ ownership structures and promoting high-quality enterprise development.